Digital Narratives as Emotional Scaffolds: A Case Study of Student-Generated Stories in Thai ESL Classrooms - Pong Krit; Rit Som; Siri Lek (Journal Emerging Technologies in Education, 2025)
Background. The increasing integration of digital storytelling in English as a Second Language (ESL) education highlights its potential not only for linguistic development but also for emotional expression among learners. Purpose. This study investigates how digital narratives created by Thai ESL students function as emotional scaffolds in language learning environments. The research aims to explore the affective dimensions of student-generated digital stories, specifically how these narratives foster emotional engagement, self-expression, and learner identity in the ESL classroom. Method. Using a qualitative case study approach, data were collected through interviews, classroom observations, and content analysis of student projects. Results. Findings indicate that digital storytelling enabled students to externalize personal experiences, reduce language anxiety, and build emotional connections with the learning content. Furthermore, the process encouraged collaborative dialogue and empathy among peers. Conclusion. The study concludes that digital narratives serve as both pedagogical and emotional tools, bridging language skills with psychological well-being. Implications suggest that ESL educators should intentionally design digital storytelling tasks to support students' emotional development alongside language proficiency.